Matsutake worlds - Faier, Lieba; Hathaway, Michael J.; Hathaway, Michael J. (Studies in Social Analysis Ser., 2021)
"The matsutake mushroom continues to be a highly sought delicacy, especially in Chinese, Japanese, and Korean cuisine. Matsutake Worlds explores this mushroom through the lens of multi-species encounters centered around the matsutake's notorious elusiveness. The mushroom's success, the contributors of this volume argue, cannot be accounted for by any one cultural, social, political, or economic process. Rather, the matsutake mushroom has flourished as the result of a number of different processes and dynamics, culminating in the culinary institution we know today"--